Activity- and taxonomy-based knowledge representation framework. (9th October 2008) - Marte, Birgit; Steiner, Christina M.; Heller, Juergen; Albert, Dietrich
Elaborations of Competence-based Knowledge Space Theory (CbKST) incorporate skills that refer to the conceptual information of the domain as well as to the activities learners are expected to perform in this context. Thus, they are suggested as a formal knowledge representation framework that is able to take into account current activity-oriented pedagogical trends in designing effective Units of Learning (UoL). The broad array of required behaviour to be achieved by learners demands a search for instruments like taxonomies that allow for conceptualising activities, and consequently, skills and learning objectives. It is shown that the availability of such a taxonomy-based framework may be utilised in order to enhance the access and interface functionalities of learning systems. In particular, the selection of proper learning units and the delivery of effective feedback mechanisms on the teaching and learning progress are facilitated.